2017
DOI: 10.20546/ijcrbp.2017.408.008
|View full text |Cite
|
Sign up to set email alerts
|

Moringa oleifera: A Miracle Multipurpose Potential Plant in Health Management and Climate Change Mitigation from Bahraich (UP) India - An Overview

Abstract: Moringa oleifera known as -horseradish tree‖ or -drumstick tree‖, native to India, is one of the best useful tree and with an enormous amount of benefits in the world. Numerous research reports have appeared in different national and international scientific journals by studying its nutritional and medicinal properties of Moringa over the past decades. Different reports show that due to its multipurpose uses Moringa tree has recently got attention in different countries. Moringa oleifera is a tree that is some… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 38 publications
1
3
0
Order By: Relevance
“…However, in this study, competition for growing space and light was not observed. This observation supports the claim made by Mall & Tripathi (2017) that there is not much competition for light when plants are between 1.6 and 2.0 meters tall. Additionally, Amaglo et al (2006) came to the conclusion that M. oleifera, as a thriving plant crop, exhibited considerable increases in the number of leaves developed and average plant height.…”
Section: Plant Heightsupporting
confidence: 91%
“…However, in this study, competition for growing space and light was not observed. This observation supports the claim made by Mall & Tripathi (2017) that there is not much competition for light when plants are between 1.6 and 2.0 meters tall. Additionally, Amaglo et al (2006) came to the conclusion that M. oleifera, as a thriving plant crop, exhibited considerable increases in the number of leaves developed and average plant height.…”
Section: Plant Heightsupporting
confidence: 91%
“…Increase in relative organ weight (heart and brain) of rats during training session, resulting from administration of Moringa extract may indicate the improvement in the nutritional state of the animal. Moringa leaves have a long history as an herbal remedy, and nutritious addition to the diet (Mall and Tripathi, 2017). Moringa leaves are an excellent source of protein, and are rich in metabolisable energy, vitamins, minerals, fats, and contain the 10 amino acids essential to man (Oyeyinka and Oyeyinka, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…They are an excellent source of protein, metabolisable energy, vitamins (A, B, C, E), minerals, and contain the 10 amino acids essential to man (Lamou et al, 2016). M. oleifera leaves are used in traditional medicine to treat malnutrition, fever, headaches, nerve pain, diabetes and many other diseases (Mall and Tripathi, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Antifungal, abortifacient, antibacterial, and emmenagogue properties are all found in the bark. Bark can be used for tanning and also produces a coarse fiber 37 .…”
Section: Leavesmentioning
confidence: 99%